PENINGKATAN HASIL BELAJAR SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) DENGAN MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) - Waltialan, Nengsi; Mataheru, Wilmintjie; Huwaa, Novalin C (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2022)
This study aims to determine the improvement of student learning outcomes on the material of two-variable linear equation system by applyning the Think Pair Sharelearning model. The subjects in the study were all eighth grade students of SMP Kristen Tounwawan with a total of 20 students. This research is a Classroom Action Research with the teacher acting as a teacher acting as a teacher and lasts for 3 cycles. Data was collected using tests and observations. The data analysis technique uses quantitative analysis and quantitative analysis. The results of the analysis showed that there was an increase in student learning outcomens from the first cycle, 25% (5 students) who achieved the KKM 60. to the second cycle 42,85% (9 students) who reachd the KKM 60 and the cycle, 85% (17 students) who reach KKM 60. From the results obtained, the coopeative learning model of the material of a two-variable linear equation system.